Social Assessment of Policies for Labour, Educational and Cultural Integration of Immigrants in Bulgaria - Hristov, Yoan (Research Papers, 2016)
The integration of immigrants in the Bulgarian society rises as a key issue for the European development of Bulgaria. To achieve the necessary results, integration policies need serious optimization. It is necessary to create mechanisms for effective implementation of the measures to deal with the challenges of the time related to migration pressure on the country.The findings of the study of policies for employment, educational and cultural integration of immigrants in the Bulgarian society can serve to correct some measures applied and implemented practices and replacing them with more adequate and appropriate actions. Results could contribute to the effectiveness of ongoing policies, to streamline the process of their realization and to optimize the impact of integration activities and measures.Successful integration requires policy interventions, which are consistent with the government priorities, but also with international commitments. Of particular importance is the Bulgarian statesmen engaged in the formulation and implementation of integration policies to show political will to implement them in practice and making them reality.
Keywords: Integration; Migration; Immigrants; Public policy